Redescription of the numbat tick Ixodes (Sternalixodes) myrmecobii Roberts, 1962 (Acari: Ixodidae) with descriptions of the male and nymph, and new host records - Kwak, Mackenzie L.; Ash, Amanda; Elliot, Aileen (Zootaxa, 2017)
Limited knowledge regarding the biology and identification of the Australian tick Ixodes myrmecobii exists with only the female described to date. Here we provide a description of the male and nymph as well as a redescription of the female. All described stages are molecularly characterised using the cytochrome c oxidase subunit 1 (CO1) and internal transcribed spacer 2 (ITS2) loci. An updated list of hosts is presented including the first records from humans, cattle and several native species. Information on the distribution and conservation status of this species is also included.